Public Finance and the Compound-Interest Principle - Bullock, C. J. (Quarterly Journal of Economics, 1938)
Pareto on the compound-interest principle, 641.— Increase of the foreign trade of the United States analyzed, 643.— The per capita figures, 647.— Increase of bank clearings, mining output, and manufacturing output, 649.—Increase of per capita expenditures of the federal government, 651.— Devaluation of the dollar, 652.— Increase of the national debt, 653.—Comparison with growth of foreign trade, 655.— Conclusion, 657.